PENGARUH PERINGATAN BAHAYA MEROKOK PADA KEMASAN ROKOK TERHADAP PERILAKU PEROKOK - Miftahussurur, Miftahussurur; Darmawan, Arif; Soenarjanto, Bagus (representamen, 2018)
This study was aimed to determine the effect of hazard warning on cigarette packs for disease asimpact on smoking among students at University of August 17, 1945 in Surabaya. Data collection wasdoing by spread questionnaires as many as 78 people respondents. Data analysis technique used wastechnique of correlation by Pearson’s product moment. The results showed that the correlation of theresults coefficient by - 0.296. This suggests that the negative relationship between warning the dangers ofsmoking to smokers behavior on August 17, 1945 students at the University of Surabaya. This negativerelationship means relations of "no strong enough", because the number of correlation coefficients wereobtained at intervals of -0.4 until –0.2. The results also showed that t count <-ttable (-2.6837 <-1.655) thenH0 is rejected or H1 is accepted, that there is a significant negative relationship between hazard warningson packs of cigarettestoward smokers’ behavior on students of University of August 17, 1945 in Surabaya.Keywords: warning, dangers, smoking, behaviour, cigarettes.